Climate as the Main Driver of Large‐Scale Genetic Patterns and Connectivity in the Expanding Golden Jackal - Alejandro Flores‐Manzanero; Wiesław Bogdanowicz; Milomir Stefanović; Roya Adavoudi; Rasoul Khosravi; Francelly Martínez‐Sosa; Karolina Doan; Yellapu Srinivas; Ovidiu C. Banea; Duško Ćirović; Gianluca D'Amico; Mihajla Djan; et al. (Global Change Biology, 2026)
Rapid global changes in climate and habitats lead to shifts in species' geographic ranges. Range contractions experienced by numerous species may result in local extinctions and connectivity disruptions. In some species, range expansions have been observed instead, suggesting the enlargement of suitable habitats and/or adaptations to changing environments. Despite its importance for wildlife management, our understanding of the factors influencing species' spatial responses to rapidly changing environments remains limited. The golden jackal serves as an excellent model to address this knowledge gap, given its ongoing rapid range expansion. In this study, we investigated environmental factors contributing to genetic connectivity and local adaptation across the expanding range of the golden jackal, based on a comprehensive sampling scheme across Eurasia ( n = 363), a high‐quality set of genomic markers (19,746 SNPs), and a landscape genomics framework. At the continental scale, geographic distance emerged as the predominant factor. At finer spatial scales, genetic connectivity was best explained by climatic predictors, specifically high annual and seasonal variations in precipitation and temperature, which can shape the species' spatial genetic structure by constraining gene flow. Our connectivity models for current and future climatic conditions show that the species' northward expansion is facilitated by changes in these variables in central and northern Europe promoting high connectivity. Precipitation and temperature were also responsible for most local adaptation signals. Given the potential role of hybridization with domestic dogs in shaping range expansion patterns, we investigated the association between environmental conditions and dog admixture proportions. We found no significant trends, indicating a limited effect of dog admixture on habitat choice. Collectively, our findings suggest that the golden jackal has the potential to continue its expansion across Eurasia in response to ongoing global climate change, providing an example of a species that rapidly tracks the expansion of its suitable habitats.